PENYEBARAN SERANGGA PADA AREAL PERTANAMAN EUKALIPTUS (Eucalyptus alba) HUTAN LINDUNG GUNUNG NONA DESA URIMESING KOTA AMBON - Hindun Samanery; Fransina Latumahina; Cornelia Wattimena (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Research on the Distribution of Insects in the Eucalyptus (Eucalyptus alba) Planting Area of ​​the Mount Nona Protected Forest, Urimesing Village, Ambon City aims to find out 1) To inventory the types of insects that live in the Eucalyptus (Eucalyptus alba) planting area of ​​the Gunung Nona Protected Forest, Urimesing Village. 2) To determine the value of abundance, diversity and distribution of insects in the Eucalyptus (Eucalyptus alba) planting area of ​​Mount Nona Protected Forest, Urimesing Village. 3) To identify factors that influence the spread of insects in the Eucalyptus (Eucalyptus alba) planting area of ​​Mount Nona Protected Forest, Urimesing Village. This research was carried out descriptively quantitatively, data collection used the exploratory method. Processing insect data by calculating the insect diversity index value (H`) is 0.902, the abundance value (K) is 0.787, the evenness index value (E) is 0.361, the dominance index value (C) is 0.052, and the moricity index value is 0.703. The five index values ​​indicate that the insect species is classified as low.